Behaviour Change Interventions For Physical Activity In Adults With Chronic Obstructive Pulmonary Disease; A Systematic Review And Meta-Analysis - Malathi, G.; Sarathi, Sathiyalatha; Hemavathy, V. (Journal of Neonatal Surgery, 2025)
Chronic obstructive pulmonary disease (COPD) is a progressive respiratory condition that significantly limits physical activity, adversely affecting the quality of life and overall health outcomes for affected individuals. This systematic review and meta-analysis aim to evaluate the effectiveness of behavior change interventions (BCIs) designed to increase physical activity among adults with COPD. A comprehensive literature search was conducted across major databases, identifying studies that employed BCIs, including motivational interviewing, self-monitoring techniques, and technology-based support, to facilitate engagement in physical activity. A total of seven studies met the inclusion criteria and were synthesized to explore the impact of these interventions on physical activity levels and health-related quality of life. Findings revealed that multimodal interventions, combining exercise promotion with behavioral coaching and psychological support, resulted in statistically significant increases in physical activity levels (Cohen's d range: 0.39 to 0.74) compared to control groups. Moreover, interventions that incorporated ongoing support exhibited better sustainability of physical activity gains over time. This study underscores the importance of individualized, multidimensional strategies in promoting physical activity among COPD patients, suggesting that the integration of BCIs in clinical practice can enhance health outcomes and quality of life. Further research is warranted to establish standardization in intervention approaches and to identify the most effective components of BCIs within diverse patient populations.